(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
Mangroves is one of the producers of nutrients, one of which is nitrate in estuary waters. Nitrate content in waters naturally comes from weathering or decomposition of plants and the remains of dead organisms. This study aims to analyze the relationship between mangrove density and nitrate in the mangrove ecosystem on Manomadehe Island, South Jailolo, West Halmahera. Data collection was carried out from April to May 2022. Analysis of sediment samples was carried out at the LPPM Basic Laboratory, Khairun University. The data analysis method used is simple linear regression. The results of the analysis of the highest species density at ST3 were 4100 trees/ha-1 and the lowest was ST1 at 1900 trees/ha-1. The highest nitrate concentration was found at ST3 at 3.58 mg/kg and the lowest at ST1 at 0.83 mg/kg. The strong ridge pattern (r) between the variable density and the nitrate concentration was 88.90%. The regression coefficient of 1.8998 indicates that the density of species has a positive relationship with the average concentration of nitrate in the sediment, where every 1 unit decreases in the value of mangrove species density will affect the decrease in the average nitrate of -1.33812 units.